Hall effect sensor for measuring metal particles in lubricant - Chaiyachit, C.; Satthamsakul, S.; Sriratana, W.; Suesut, T. (My University, 2012)
This paper presents the development of hall effect sensor for measuring the contamination of lubricant in industry. This technique is based on the principle of the magnetic field and Hall Effect. The magnetic field is made up of a permanent magnet which is measured by a Hall Effect sensor. The measured magnetic field can be estimated the level of contaminants in the oil by the ferrous particles which indicate a lifetime of lubricant. Therefore, this issue is taken into account to identify the suitable time for draining (refer to NASI 638 standard). The experimental results were performed to demonstrate the output voltage of the Hall Effect sensor relating to the level of the metal particles in the lubricant. Our instrument is low cost and it can be applied in the factory, machinery, automobile, oil industry as well.
Keywords: Hall effect sensor; Lubricant quality measurement; Magnetic measurement